Community Empowerment Strategies in Developing Sustainable Marine Tourism at Kahona Beach - Amrullah, Amrullah; Adi Junaidi, Muhammad; Walid Sugandi, Yogi Birrul (Sumber Belajar Sejahtera, 2025)
This study aims to formulate strategic directions for sustainable marine tourism development at Kahona Beach, located in Sekaroh Village, Jerowaru District, East Lombok, by emphasizing community empowerment and digital innovation. Employing a descriptive qualitative approach with a case study design, the research targeted key tourism stakeholders in the village. The study population included local tourism operators, community leaders, youth organizations, and village residents. Six informants were selected purposively based on their direct involvement and knowledge. Data were collected through participatory observation, in-depth interviews, documentation review, and visual data analysis. Thematic analysis using Braun and Clarke’s six-phase model was applied, complemented by SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to explore strategic development potential. Findings revealed that Kahona Beach possesses strong ecological and cultural assets, such as healthy coral reefs and vibrant traditions, which support its potential as a marine ecotourism destination. However, internal challenges include underdeveloped infrastructure, limited digital marketing, and low community engagement. External threats involve privatization of coastal access and ecological degradation, yet opportunities are present through rural tourism programs, digital technologies, and increasing demand for nature-based travel. The study recommends the establishment of inclusive tourism institutions, digital training for local youth, and participatory strategies for environmental and cultural preservation. These findings contribute to the discourse on community-based marine tourism and offer practical insights for local governments and policymakers seeking sustainable and inclusive destination governance.